2017
DOI: 10.1016/j.snb.2016.07.063
|View full text |Cite
|
Sign up to set email alerts
|

A study of MHD-based chaotic advection to enhance mixing in microfluidics using transient three dimensional CFD simulations

Abstract: Building on our previous work on transient, two dimensional simulations of the Navier-Stokes equations to investigate mixing enhancement by introducing the Lorentz force in MHD as a control parameter to create turbulentlike chaotic advection, this paper describes transient, three-dimensional simulations. Our approach differs from many previous analytical investigations by other workers based on potential flow and linearized stokes flow. A shallow disk-ring cylindrical microfluidic cell with gold electrodes dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…As it has been reported [1,[7][8][9] in the micro-scale, mixing can be improved by "chaotic advection", which involves breaking, stretching, and folding of liquid streams leading to an increase of the interfacial contact area of the fluids. In our laboratory, the mixing efficiency of several types of passive μ-mixers was investigated both experimentally and numerically [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been reported [1,[7][8][9] in the micro-scale, mixing can be improved by "chaotic advection", which involves breaking, stretching, and folding of liquid streams leading to an increase of the interfacial contact area of the fluids. In our laboratory, the mixing efficiency of several types of passive μ-mixers was investigated both experimentally and numerically [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%
“…Several comprehensive reviews of µ-mixing devices and their principles can be found in the relevant literature [1][2][3][4][5][6]. As it has been reported [1,[7][8][9] in the micro-scale, mixing can be improved by "chaotic comprehensive reviews of μ-mixing devices and their principles can be found in the relevant literature [1][2][3][4][5][6]. As it has been reported [1,[7][8][9] in the micro-scale, mixing can be improved by "chaotic advection", which involves breaking, stretching, and folding of liquid streams leading to an increase of the interfacial contact area of the fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, mixing process is investigated experimentally or by numerical of some passive scalars, while less numerical research has been done on analysis of mixing characteristics in MHD flows. [14][15][16] In this article the effect of uniform and constant external magnetic field in mixing properties of isotropic MHD flow is investigated by analyzing large and small scale eddies dynamics; In order to explore mutual interaction of velocity and magnetic field, MHD flow with moderate magnetic Reynolds number is considered and solved by use of DNS. The results of this research can be useful in phenomenology and also prediction of mixing behavior of some industrial equipment as well as natural phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Its principle of operation is based on the Lorentz force acting in an electrical conductive solution, in the presence of magnetic and electric fields, resulting in a motion flow. The most used solutions in the beginnings of MHD research were liquid metals and ionized gases, though in the more recent scientific literature electrolyte solutions have made an incursion [ 2 ]. This is because the flow in a MHD stirrer depends on the solution electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%